Preservation of Traditional Sanskrit Teaching Among the Sri Lankan Tamils: Current Status and Future Perspectives - Balakailasanathasarma, M. (University of British Columbia, 2018)
Sri Lanka has a rich tradition in Sanskrit education over the years and currently it is institutionalized. Sri Lankan tamils are natives of the South Asian island state of Sri Lanka. Most of Sri Lankan tamils in Sri Lanka live in the northern and eastern provinces and minority throughout the rest of the country. Sri Lankan tamils have a rich tradition in traditional Sanskrit teaching. Objective of this study is to identify some evidences of traditional sanskrit teaching among the Sri Lankan tamils through cases studies and other historical evidence. Findings of this study outline the History of Traditional Sanskrit Teaching among the Sri Lankan Tamils starts initially from Eighteenth century. Traditional Sanskrit Teaching initially rooted from temple-based system of education and the oral traditions among Sri Lankan Tamils. The Core elements of this teaching tradition depend on two groups. i.e. traditional organizations and religious persons. This study identified more than twenty Traditional organizations. Under this tradition Gurukula system were revived. Examples of these tradition include Prabōdha Gunōdaya Samskruta Vidyalayam, Saiva prakāsa vidyāsālai, Ārya Drāviḍa Bhāṣhā abhivirddhi Sankam, Cunnākam Sadāsiva prācīņa pāṭhasālai, Brāmmaṇa Samājam, Sivāṇanda Gurukulam, Ganapatisvara Gurukulam, Mummoli kävya pāṭhasālai, Sri Lanka Gurubramma vidyarti Sabai, Sri Vidya Gurukulam, Dharma Śästhā Gurukulam, and etc, which contributed for this tradition under the first category, and more than thirty personal teaching efforts under the second category. This tradition passed from this traditional organizations into the hands of Universities, themselves run on different medium of instruction, it will become very rare indeed to find anyone taught or capable of teaching in the old traditional way. This study suggests making necessary steps to preserve this tradition with the support of temples and other religious organizations.